The multiple factors of suboptimal early feeding practices among infants aged 0–5 months in Indonesia - Titaley, Christiana Rialine; Wijayanti, Ratna U.; Mu'asyaroh, Anifatun; Ariawan, Iwan (Frontiers in Nutrition, 2023)
Background: Optimal early infant feeding practices are critical to ensure adequate nutrition for infants’ growth and development. This study aimed to examine the determinants of suboptimal early feeding practices (i.e., delayed initiation of breastfeeding, prelacteal feeding, and non-exclusive breastfeeding) among infants aged 0–5 months in Indonesia. Methods: We used data collected in the 2012 and 2017 Indonesia Demographic and Health Surveys. Analyses were conducted using information from 3,198 live-born singleton infants aged 0–5 months. The primary outcomes used were: (1) delayed initiation of breastfeeding in the first hour after birth; (2) prelacteal feeding in the first three days; and (3) non-exclusive breastfeeding in the last 24 hours preceding the survey. Potential predictors analyzed were categorized into the environmental, household, maternal, pregnancy, delivery, and child characteristics. Logistic regression analyses were performed to identify factors significantly associated with each outcome. Results: Approximately 78,6% of infants aged 0–5 months in Indonesia had at least one of the three suboptimal early infant feeding practices. We found a strong association between the three outcome indicators analyzed. The determinants of delayed initiation of breastfeeding included infants from Sumatera region (adjusted odds ratios (aOR)=2.02, p<0.001), infants delivered by Caesarean section (aOR=2.78, p<0.001), and in non-health facilities (aOR=1.53, p=0.003). The determinants of prelacteal feeding in the first three days included infants living in urban areas (aOR=1.32, p=0.035), the first birth-ranked infants (aOR=1.32, p=0.019), and infants who had delayed initiation of breastfeeding in the first hour of life (aOR=3.90, p<0.001). The determinants of non-exclusive breastfeeding in the last 24 hours included infants whose mothers worked in non-agricultural fields (aOR=1.52, p<0.001), infants delivered by Caesarean section (aOR=1.33, p=0.044), and the first birth-ranked infants (aOR=1.28, p=0.039). Conclusions: There was a high percentage of infants aged 0-5 months who had suboptimal feeding practices in Indonesia. As we found multiple factors associated with suboptimal early feeding practices among infants, integrated approaches, including health promotion and supportive public policy, are required to ensure infants receive adequate nutrition in the early stages of life.